Alzheimer’s Disease and Inflammation Research: A Systematic Bibliometric Review and Network Visualization of the Published Literature Between 2000 and 2023 - Azman, Khairunnuur Fairuz; Ismail, Che Aishah Nazariah; Shafin, Nazlahshaniza; Zakaria, Rahimah (Recent Advances in Inflammation & Allergy Drug Discovery, 2025)
<span class=
Keywords: inflammation